Enhancing Gut Microbiome focusing on Anti-Inflammatory Foods, Dietary Fiber, and Polyphenols - Janis Z.; Sharma Sunayan (BIO Web of Conferences)
The gut microbiome, a complex ecosystem of diverse microbial species residing in the gastrointestinal tract, plays an integral role in maintaining human health. Often referred to as a “vital organ,” the gut microbiome influences various physiological processes, including nutrient metabolism, immune regulation, and neural communication. Its composition, shaped by genetic, dietary, and environmental factors, is crucial for sustaining overall homeostasis. Balanced gut microbiota supports digestion, synthesizes essential nutrients such as short-chain fatty acids (SCFAs), vitamins, and amino acids, strengthens the intestinal barrier, and communicates with the central nervous system through the gut-brain axis, impacting cognitive and mental health. Conversely, gut dysbiosis—marked by an imbalance in beneficial and harmful bacteria—has been linked to metabolic disorders, autoimmune diseases, inflammatory bowel diseases (IBD), and neurodegenerative conditions. The potential of particular dietary treatments, such as the Mediterranean diet, low-FODMAP diets, and fiber-rich foods, in modifying microbial composition and fostering gut health is highlighted by recent research that highlights the reciprocal relationship between diet and gut microbiota. Furthermore, anti-inflammatory, prebiotics, and polyphenols-rich foods show encouraging therapeutic promise in improving immunological, metabolic, and neurological processes as well as reducing gut dysbiosis. This review looks at the dynamic relationship between gut microbial diversity, dietary patterns, and systemic health to shed light on how specific nutritional strategies may be used as therapeutic and preventative measures to enhance gut health and lower the risk of chronic diseases.